TSA for Germany: database of the satellite account and perspectives for integration into a sectoral disaggregated macro-econometric model - Gerd Ahlert (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2004)
The Institute of Economic Structures Research (GWS mbH) has developed a tourism satellite account (TSA) for the Federal Republic of Germany relating to the year 2000.1 In the process of elaborating the TSA the Federal Statistical Office (as an external partner outside the GWS) has been fully integrated and provided partially unpublished data. In the first part of the paper major steps in calculating the monetary TSA-tables 1 to 6 are presented. It will be shown how this specific nformation has been used in the process of TSA preparation and what empirical results are obtained to the year 2000 for Germany. In the last part of the paper the structure of the tourism economic simulation and forecasting model VOYAGE is presented. GWS has gained experience in such a theme-specific macroeconomic modelling approach. The model VOYAGE is based on the German TSA for the year 2000 which will be consistently integrated into the German INFORGE model. Its performance is founded on the INFORUM philosophy to build econometric input-output models bottom up and fully integrated. The model YOYAGE with its tourism economic extensions can be used e. g. for analysing the economic impacts of behaviour modifications in tourism or of big events.
Keywords: L83; 330; TSA; Germany; tourism satellite account; perspectives for integration; macro-econometric model